Estrogen receptor alpha signaling in extrahypothalamic neurons during late puberty decreases bone size and strength in female but not in male mice. Issue 5 (2nd April 2020) - Kim, Na Ri; Jardí, Ferran; Khalil, Rougin; Antonio, Leen; Schollaert, Dieter; Deboel, Ludo; van Lenthe, G. Harry; Decallonne, Brigitte; Carmeliet, Geert; Gustafsson, Jan‐Åke; Claessens, Frank; Ohlsson, Claes; et al.
Abstract: Sexually dimorphic bone structure emerges largely during puberty. Sex steroids are critical for peak bone mass acquisition in both genders. In particular, the biphasic effects of estrogens mediate the skeletal sexual dimorphism. However, so far the stimulatory vs inhibitory actions of estrogens on bone mass are not fully explained by direct effects on bone cells. Recently, it has become evident that there is possible neuroendocrine action of estrogen receptor alpha (ERα) on the skeleton. Based on these considerations, we hypothesized that neuronal ERα‐signaling may contribute to the skeletal growth during puberty. Here, we generated mice with tamoxifen‐inducible Thy1‐Cre mediated ERα inactivation during late puberty specifically in extrahypothalamic neurons (N‐ERαKO). Inactivation of neuronal ERα did not alter the body weight in males, whereas N‐ERαKO females exhibited a higher body weight and increased body and bone length compared to their control littermates at 16 weeks of age. Ex vivo microCT analysis showed increased radial bone expansion of the midshaft femur in female N‐ERαKO along with higher serum levels of insulin‐like growth factor (IGF)‐1 as well as IGF‐binding protein (IGFBP)‐3. Furthermore, the 3‐point bending test revealed increased bone strength in female N‐ERαKO. In contrast, inactivation of neuronal ERα had no major effect on bone growth in males. In conclusion, we demonstrate that central ERα‐signaling limits longitudinal bone growth and radial bone expansion specifically in females potentially by interacting with the GH/IGF‐1 axis.